2018
DOI: 10.31349/revmexfis.64.566
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of argon pressure as an option to control transmittance and resistivity of ZnO:Al films deposited by DC magnetron sputtering: on the dark yellow films at 10-7 Torr base pressures

Abstract: In a previous paper, we reported that thin films of ZnO:Al [aluminum-zinc oxide (AZO)] deposited after achieving a very low base pressure [from 4.0×10–7 Torr (5.6×10–5 Pa) to 5.7×10–7 Torr (7.6×10–5 Pa)] result dark yellow in color and are resistive. These are undesirable characteristics for the application of AZO thin films as front electrodes in solar cells. However, given the increasingly tendency in the acquisition of equipment that allow us to reach excellent vacuum levels, it is necessary to find the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Shain et al 23 observed (002) peak of ZnO when deposited AZO thin films by changing argon pressure from 10 to 30 sccm, moreover, they noticed that there was no impurity of aluminium seen in XRD patterns, and with the rise in argon pressure, the intensity of the peak diminished. The increase in the intensity of the (002) peak with the decrease in the argon partial pressure were also observed by other researchers [24][25][26] .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Shain et al 23 observed (002) peak of ZnO when deposited AZO thin films by changing argon pressure from 10 to 30 sccm, moreover, they noticed that there was no impurity of aluminium seen in XRD patterns, and with the rise in argon pressure, the intensity of the peak diminished. The increase in the intensity of the (002) peak with the decrease in the argon partial pressure were also observed by other researchers [24][25][26] .…”
Section: Resultssupporting
confidence: 84%
“…In their research on the effects of argon pressure, Wang et al 28 found that the films that were deposited were transparent and had a maximum value of 85%, which diminished when the pressure was reduced from 2.5 Pa to 0.5 Pa. Valenzuela et al 26 noticed a similar trend and reported that the optical transmittance improved and the electrical characteristics deteriorated with a rise in argon flow rate but without oxygen addition. Tseng et al 30 also observed 80% transmittance at 193 sccm argon flow rate which decreased at the argon flow rate was reduced to 33 sccm.…”
Section: Resultsmentioning
confidence: 90%
“…To analyze the oxidation states of zinc and aluminum in different ZnO film samples, high-resolution XPS spectra were obtained for Zn 2p 3/2 core levels, showing a major Zn p1 peak located at 1021.69 eV and a minor Zn p2 peak located at 1022.47 eV (Figure S1a). Zn p1 is attributed to the crystalline lattice of ZnO, and Zn p2 , to interstitial defects or zinc hydroxide bond (Zn–OH) species. , It is observed that the presence of the AlO x layer increases the relative intensity of the Zn p2 peak, suggesting an increase of interstitial defects close to the surface of ZnO and ZnO:Al films, probably by the diffusion of aluminum atoms. On the other hand, the high-resolution XPS spectra for the Al 2p peak is found at 74.22 eV in ZnO:Al, ZnO/AlO x and ZnO:Al/AlO x samples (Figure S1b), and the relative intensity of this peak is higher for ZnO/AlO x and ZnO:Al/AlO x samples than that for ZnO:Al.…”
Section: Resultsmentioning
confidence: 99%